2022
DOI: 10.1007/s00521-022-06935-w
|View full text |Cite
|
Sign up to set email alerts
|

Selection of suitable distance education platforms based on human–computer interaction criteria under fuzzy environment

Abstract: The rapid spread of the COVID-19 pandemic has affected not only the health industry but also the education sector. E-learning systems have recently become a compulsory part of all education institutions, including schools, colleges, and universities worldwide because of the COVID-19 pandemic crisis. The objectives of the current study were twofold: (1) to conduct an analytical approach for ranking of distance education platforms based on human–computer interaction criteria and (2) to identify the most appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The findings showed that a student's academic success was related to their perceptual modality preference. Adem et al [102] focused on the human-computer interaction among students for a more applicable platform during distance learning. Their study highlighted that the need to re-assess and consider appropriate platforms for e-learning should be examined as these affect students' performance.…”
Section: Limitations and Future Usementioning
confidence: 99%
“…The findings showed that a student's academic success was related to their perceptual modality preference. Adem et al [102] focused on the human-computer interaction among students for a more applicable platform during distance learning. Their study highlighted that the need to re-assess and consider appropriate platforms for e-learning should be examined as these affect students' performance.…”
Section: Limitations and Future Usementioning
confidence: 99%
“…He analyzed the changes in the learning system of the education industry due to COVID-19. Finally, he proposed the technical standards of human-computer interaction to analyze and evaluate the teaching quality of the education platform [8]. Yang expounded on the function and structure of the existing navigation system using human-computer interaction technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the ultimate purpose of the entire affective computing model is to be able to discriminate the selected effective features, proper classification model selection is very necessary ( Adem et al, 2022 ). There are many kinds of classification models, and this paper chooses LDA as the basic classifier.…”
Section: Emotional Interaction Algorithm Based On Emotional Computingmentioning
confidence: 99%